Computed Tomographic Scan Evaluation of Pulmonary Blastomycosis. Issue 4 (2009) - Ronald, Suzanne; Strzelczyk, Jacek; Moore, Sean; Trepman, Elly; Cheang, Mary; Limerick, Bill; Wiebe, Lyle; Sarsfield, Pete; MacDonald, Kerry; Meyers, Michael; Embil, John M
Abstract : BACKGROUND: Blastomycosis is an uncommon granulomatous pulmonary and extrapulmonary infectious disease caused by the thermally dimorphic fungus Blastomyces dermatitidis . Diagnosis may be delayed or difficult because of varied presentation. The characteristics of blastomycosis on computed tomographic (CT) scan of the chest are not well characterized. METHODS: The images from 34 chest CT scans from patients with confirmed pulmonary blastomycosis were retrospectively reviewed. RESULTS: The most common CT findings were air bronchograms in 22 patients (65%), consolidation in 21 patients (62%), nodules (smaller than 3 cm) in 21 patients (62%) and lymph node enlargement (mediastinal and hilar nodes combined) in 12 patients (35%). Only four patients (12%) had a miliary pattern. CONCLUSIONS: A specific abnormality characteristic of pulmonary blastomycosis was not identified on CT scanning. The diagnosis can only be made in the context of a high index of clinical suspicion with histological or culture confirmation.